2020
DOI: 10.3389/fnagi.2020.00039
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of Inferior Parietal Lobule During Sensory Gating in Patients With Amnestic Mild Cognitive Impairment

Abstract: Patients with amnestic mild cognitive impairment (aMCI) demonstrate significant cognitive deficits, especially in the memory aspect. The memory deficiency might be attributed to the difficulties in the inhibitory function to suppress redundant stimuli. Sensory gating (SG) refers to the attenuation of neural responses to the second identical stimulus in a paired-click paradigm, in which auditory stimuli are delivered in pairs with inter-stimulus intervals (ISI) of 500 ms and inter-pair intervals of 6-8 s. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…A study demonstrated that M50 sensory gating (SG) deficits in the IPL were related to the poorer performance in the immediate recall of logic memory (LM). Obviously, patients with MCI showed lower auditory short-term memory function with the deficit in the IPL in clinical manifestations ( Cheng et al, 2020 ). It can be concluded that decreased ReHo can be related to the clinical manifestations of patients with MCI.…”
Section: Discussionmentioning
confidence: 99%
“…A study demonstrated that M50 sensory gating (SG) deficits in the IPL were related to the poorer performance in the immediate recall of logic memory (LM). Obviously, patients with MCI showed lower auditory short-term memory function with the deficit in the IPL in clinical manifestations ( Cheng et al, 2020 ). It can be concluded that decreased ReHo can be related to the clinical manifestations of patients with MCI.…”
Section: Discussionmentioning
confidence: 99%
“… 34 LM: a brief story was spoken to the subject to measure immediate and delayed recall memory function. 35 DSB: a series of digits were spoken to the subject to measure the auditory working memory. 36 …”
Section: Methodsmentioning
confidence: 99%
“…LM: a brief story was spoken to the subject to measure immediate and delayed recall memory function. 35 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous event‐related potential (ERP) studies have demonstrated the disruption of P50 SG in patients with AD (Jessen et al., 2001; Josef Golubic et al., 2017; Thomas et al., 2010). By magnetoencephalographic (MEG) recordings, we have previously found that compared to healthy older adults, patients with amnestic MCI exhibited reduced M50 and M100 SG function in the right inferior parietal lobule (IPL), as well as reduced M50 SG function in the left inferior frontal gyrus (Cheng et al., 2020). However, to the best of our knowledge, there have been no studies investigating the effects of SMC on auditory SG.…”
Section: Introductionmentioning
confidence: 99%